2010
DOI: 10.1021/nl102069z
|View full text |Cite
|
Sign up to set email alerts
|

DNA Translocation through Graphene Nanopores

Abstract: In the past few years, nanopores have emerged as a new powerful tool to interrogate single molecules. They have been successfully used to rapidly characterize biopolymers like DNA 3,4 , RNA 5 , as well as DNA-ligand complexes 6 and local protein structures along DNA 7 at the single-molecule level. A key driving force for nanopore research in the past decade has been the prospect of DNA sequencing. However, a major roadblock for achieving high-resolution DNA sequencing with pores is the finite length of the cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
930
4
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 936 publications
(979 citation statements)
references
References 28 publications
20
930
4
12
Order By: Relevance
“…Graphene is composed of carbon atoms that are held together by strong covalent bonds, which are theoretically predicted 35 and experimentally confirmed [36][37][38][39][40] to be impermeable to small atoms and molecules as a perfect nanoballoon at room temperature. This is a prerequisite for its bifacially nonsymmetrical modification.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Graphene is composed of carbon atoms that are held together by strong covalent bonds, which are theoretically predicted 35 and experimentally confirmed [36][37][38][39][40] to be impermeable to small atoms and molecules as a perfect nanoballoon at room temperature. This is a prerequisite for its bifacially nonsymmetrical modification.…”
mentioning
confidence: 86%
“…More importantly, we observed that the functionalities on one side are capable of influencing the chemical reactivity as well as surface wettability of the opposite side, indicative of a communication between X and Y through the mediated single carbon layer. Such novel structures would offer an excellent alternative to study asymmetric chemistry of graphene, control the selfassembly of graphene-based new functional structures 41 and advance the potential applications of graphene functional derivatives as a 2D sensor or actuator for biochemical detection 33,[38][39][40] .…”
mentioning
confidence: 99%
“…In 2010, three independent groups published experimental data of double-stranded DNA translocations through graphene nanopores [35] [36] [30]. Their approaches were equivalent: 5-25 nm diameter pores ( Fig.…”
Section: Ionic Current Detection Through a Graphene Nanoporementioning
confidence: 99%
“…As the molecules translocate they partially block ion flow through the pore, detected as a transient decrease in ionic current. Significant information (diameter, length and size) about DNA molecules was obtained through this translocation technique using graphene pores [9][10][11] .…”
mentioning
confidence: 99%